Mean Air Flow Rate and Optimum Frequency - NP, Nataraja (Journal of All India Institute of Speech and Hearing)
Optimum frequency is considered to be the frequency at which maximum physio-acoustic economy is achieved. The purpose of this study was to find out the economy in the use of air flow at optimum frequency (as determined by an objective method of locating optimum frequency).The mean air flow rate at optimum and at frequencies higher and lower than the optimum frequency were measured using an expirograph.15 male and 15 female adults were asked to phonate vowel as long as possible keeping the frequency and intensity constant, into the expirograph. Thus the mean air flow rate at optimum, + 100 Hz + 200 Hz + 50 Hz and-50 Hz from the optimum were determined. The results show that the mean airflow rate at optimum frequency was significantly lower than at other frequency levels. Therefore it was considered that there was maximum economy at optimum frequency, as determined by this method, in terms of use of air for phonation.